Unequal Regional Development in Rural Vietnam: Sources of Spatial Disparities and Policy Considerations - Long, Hoang Van (Journal of Economics and Behavioral Studies, 2013)
In Vietnam, the poor have long been assumed to be the ethnic minorities mostly living in the highlands. After more than two decades of introducing Doi moi1 policy into the economy, along with having enjoyed various improvements in social and economic aspects, the disparities between the majority and ethnic majorities, the lowlands and the highlands, and between regions, still have been widened. This paper aims at examining sources of spatial disparities in rural areas, and exploring the current situation of regional economic development using both development policy review and econometrics approaches. Data from Vietnam Household Living Standard Survey (VHLSS) 2008 was used in the study. The expenditure per capita was employed as the dependent variable to regress with household characteristics and resources in order to obtain the effecting factors. In addition, the regional dummy variables were employed to show the effects from different geographic locations. The results showed that the household characteristics and resources such as education level, perennial land area, water surface area, and the accessibility to infrastructure facilities such as road, electricity and local market had positive effect on the expenditure. Furthermore, the North Central Coastal region showed negative impact on household expenditure. Interestingly, this finding does not absolutely follow the hypothesis and indicates that the economic development strategy and polices should be adjusted to decrease the gap among regions based on their economic advantages for balancing the economic situation of the whole country in the future.